2018
DOI: 10.29244/jitl.20.1.7-12
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK HIDROLOGI TANAH DI BAWAH TEGAKAN PINUS (Pinus merkusii), MERAWAN (Hopea odorata Roxb) DAN MAHONI UGANDA (Khaya anthoteca)

Abstract: Kerusakan hutan dapat mempengaruhi fungsi hidrologi hutan sebagai pengatur tata air, menjaga waktu dan penyebaran aliran air sungai, menjaga iklim mikro, dan melindungi daerah di bawahnya dari berbagai bencana seperti banjir. Penanaman pohon kembali dinilai merupakan salah satu upaya untuk memperbaiki kondisi hutan dan lingkungan. Tujuan penelitian ini adalah untuk mengkaji karakteristik hidrologi tanah di bawah tegakan tanaman Pinus (Pinus merkusii), Mahoni Uganda (Khaya anthoteca), dan Merawan (Hopea odorata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to [12], loam-textured soils have a higher nutrient rejection ability than coarse-textured soils. Clay soil texture has optimal availability for plants, and in terms of nutrition, clay soil is better than dust-textured soil.…”
Section: Soil Texturementioning
confidence: 99%
“…According to [12], loam-textured soils have a higher nutrient rejection ability than coarse-textured soils. Clay soil texture has optimal availability for plants, and in terms of nutrition, clay soil is better than dust-textured soil.…”
Section: Soil Texturementioning
confidence: 99%
“…Deforestation and forest degradation can affect forest hydrological function. This function is essential for managing water, regulating the microclimate, and mitigating disaster [59].…”
Section: Impact On Runoffmentioning
confidence: 99%
“…Improper species determination results in water shortages and exacerbates land degradation [60]. Previous research on soil's hydrological properties reported differences in the effects of three tree species [59]. Pinus merkusii had a more significant effect on fluctuations in soil water content (3.1%) compared to Hopea odorata (2.4%) and Khaya anthotheca (1.9%).…”
Section: Impact On Runoffmentioning
confidence: 99%